Bivalent HIV-1 fusion inhibitors based on peptidomimetics. Issue 24 (15th December 2020) - Kobayakawa, Takuya; Ebihara, Kento; Tsuji, Kohei; Kawada, Takuma; Fujino, Masayuki; Honda, Yuzuna; Ohashi, Nami; Murakami, Tsutomu; Tamamura, Hirokazu
Graphical abstract: Abstract: Membrane fusion is a valid target for inhibition of HIV-1 replication. A 34-mer fragment peptide (C34), which is contained in the HIV-1 envelope protein gp41, has significant anti-HIV activity. Previously, a dimeric derivative of C34 linked by a disulfide bridge at its C -terminus was found to have more potent anti-HIV activity than the C34 peptide monomer. To date, several peptidomimetic small inhibitors have been reported, but most have lower potency than peptide derivatives related to C34. In the present study we applied this dimerization concept to these peptidomimetic small inhibitors and designed several bivalent peptidomimetic HIV-1 fusion inhibitors. The importance of the length of linkers crosslinking two peptidomimetic compounds was demonstrated and several potent bivalent inhibitors containing tethered peptidomimetics were produced.